Women’s Military Service and the Traditional Soldier Ethos - Poletyło, Marcin (Roczniki Nauk Społecznych, 2026)
After 1989, the Polish armed forces underwent a comprehensive transformation, key elements of which were professionalisation and the admission of women to the military professions. This meant a radical change in the model of the armed forces both at the level of organisation and in the sphere of axiology. The aim of this article is to identify and explore problematic areas where the traditional soldier ethos is in conflict with the new cultural norms implemented in the army with the reforms of recent decades. Existing literature on the subject and research available in the public domain on the issue of women’s military service in Poland is analysed. Three key areas were identified where tensions between old and new cultural and social norms are particularly evident. These relate to issues of masculinity, honour and sexual violence within the army.